MiR‐140 modulates the inflammatory responses of Mycobacterium tuberculosis‐infected macrophages by targeting TRAF6. Issue 8 (14th June 2019) - Li, Xiaofei; Huang, Shan; Yu, Tingting; Liang, Guiliang; Liu, Hongwei; Pu, Dong; Peng, Niancai
Abstract: This study aimed to examine miR‐140 expression in clinical samples from tuberculosis (TB) patients and to explore the molecular mechanisms of miR‐140 in host‐bacterial interactions during Mycobacterium tuberculosis ( M tb ) infections. The miR‐140 expression and relevant mRNA expression were detected by quantitative real‐time PCR (qRT‐PCR); the protein expression levels were analysed by ELISA and western blot; M tb survival was measured by colony formation unit assay; potential interactions between miR‐140 and the 3′ untranslated region (UTR) of tumour necrosis factor receptor‐associated factor 6 (TRAF6) was confirmed by luciferase reporter assay. MiR‐140 was up‐regulated in the human peripheral blood mononuclear cells (PBMCs) from TB patients and in THP‐1 and U937 cells with M tb infection. Overexpression of miR‐140 promoted M tb survival; on the other hand, miR‐140 knockdown attenuated M tb survival. The pro‐inflammatory cytokines including interleukin 6, tumour necrosis‐α, interleukin‐1β and interferon‐γ were enhanced by M tb infection in THP‐1 and U937 cells. MiR‐140 overexpression reduced these pro‐inflammatory cytokines levels in THP‐1 and U937 cells with M tb infection; while knockdown of miR‐140 exerted the opposite actions. TRAF6 was identified to be a downstream target of miR‐140 and was negatively modulated by miR‐140. TRAF6 overexpression increased the pro‐inflammatory cytokines levels and partially restored the suppressive effects of miR‐140 overexpression on pro‐inflammatory cytokines levels in THP‐1 and U937 cells with M tb infection. In conclusion, our results implied that miR‐140 promoted M tb survival and reduced the pro‐inflammatory cytokines levels in macrophages with M tb infection partially via modulating TRAF6 expression.